Microwave Pretreatment for the Extraction of Anthocyanins from Saffron Flowers: Assessment of Product Quality - Ana Álvarez; Sara Terreros; María J. Cocero; Rafael B. Mato (MDPI AG, 2021)
The potential of saffron flowers as a source of polyphenols, and in particular anthocyanins, for the extraction of bioactive compounds and the production of a cyanic colorant was analyzed. A microwave pretreatment, prior to the conventional solid-liquid extraction process, was proposed as a feasible intensification step. The effectiveness of microwave pretreatment was assessed in terms of increased yield and improved quality of the final product. The operational variables studied were the pretreatment temperature (60-120 °C) and the solid-liquid ratio (0.30-0.50 g/mL). It was found that the addition of the microwave pretreatment to the conventional process allowed one to reduce extraction time by up to 12 times and to greatly improve the characteristics of the final product, using microwave energy densities as low as 0.16-0.54 kJ/mL. The extract quality was evaluated in terms of polyphenol richness (25% increase), product composition (80% of the anthocyanins was delphinidin), antioxidant capacity (boosted by the pretreatment) and color (variations in red and blue hue depending on conditions). To conclude, a microwave pretreatment in which the material is heated to a temperature of 65 °C with a solvent ratio of 0.30 g/mL was selected as the optimum to maximize process efficiency and product quality.